2008
DOI: 10.1111/j.1474-919x.2008.00851.x
|View full text |Cite
|
Sign up to set email alerts
|

Nest predation of Common Pheasants Phasianus colchicus

Abstract: The Common Pheasant Phasianus colchicus is currently the most abundant, widespread and economically important gamebird in Europe. The Game and Wildlife Conservation Trust has undertaken several recent studies of Pheasant breeding ecology to improve the management of this species. Although predation is often the most important cause of nest failure in declining ground-nesting birds in agricultural landscapes, the causes of predation and the identity of predators are often unknown. In this paper, we analyse data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 28 publications
(51 reference statements)
0
21
1
1
Order By: Relevance
“…Predation on incubating hens during the breeding season varies between sites. Draycott et al (2008) reported 33/361 (9%) of radio-tagged hens predated on or off the nest during the breeding season at five UK sites. There was an extreme case of 80% of reared hens predated whilst nesting compared to 27% of wild-born hens at the same site (Hill and Robertson 1988a).…”
Section: Causes Of Loss and Mitigating Interventions Predationmentioning
confidence: 99%
“…Predation on incubating hens during the breeding season varies between sites. Draycott et al (2008) reported 33/361 (9%) of radio-tagged hens predated on or off the nest during the breeding season at five UK sites. There was an extreme case of 80% of reared hens predated whilst nesting compared to 27% of wild-born hens at the same site (Hill and Robertson 1988a).…”
Section: Causes Of Loss and Mitigating Interventions Predationmentioning
confidence: 99%
“…1997) and this is a central issue in another paper in these proceedings. Draycott et al . (2008) show the importance of predation at successive stages of the breeding season in the Common Pheasant Phasianus colchicus.…”
Section: Predation On Bird Populationsmentioning
confidence: 99%
“…The Ring-necked Pheasant ( Figure 1) is currently the most abundant, widespread and economically important game bird in Europe (Draycott et al, 2008). In the first half of the twentieth century there were no pheasants in Šolta Island (Mladinov, 2003), but after their introduction in the second half of the century they became very abundant (Sušić et al, 1990).…”
Section: Introductionmentioning
confidence: 98%
“…The size of the pheasant population in the island is determined by predation and hunting. Although predation is often the most important cause of nest failure in declining ground-nesting birds in agricultural landscapes, the causes of predation and the identity of predators are often unknown (Draycott et al, 2008). In the absence of predator mammals, their nests are mostly threatened by certain larger bird species particularly, corvid species that have long been considered important predators of the eggs of ground-nesting birds, including game birds (Tapper et al, 1996;Olsen and Schmidt, 2004).…”
Section: Introductionmentioning
confidence: 99%